Analisis Anggaran Pendapatan Asli Daerah Sebagai Alat Perencanaan dan Pengendalian Biaya Operasional Pada Dinas Pendapatan Kota Medan - Ingry Virnika; Ratih Anggraini Siregar (ProBisnis : Jurnal Manajemen, 2025)
The results of the study indicate that the preparation of the Local Revenue Budget (PAD) at the Medan City Revenue Office (DISPENDA) is carried out through a systematic, structured mechanism, and is based on applicable laws and regulations. Furthermore, the budget preparation process is often duplicated and lacks transparency. Therefore, efforts to address this problem include expanding public involvement in the budget planning process, for example through public consultation forums or taxpayer perception surveys.